DETERMINANT AKUNTABILITAS DANA DESA - putra, Aper prima; Srimindarti, Ceacilia; Lestar, Etty Puji (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2023)
The aims of this study are to analyze the effect of competence of human resources, internal control, use of technology and community participation on village fund accountability. The Kota Intan village community sees a lack of transparency from the village government, causing a sense of community apathy, that the authority for village development is the task of the village government. The population of this study consisted of village heads, village secretaries, BPD, section heads, heads of affairs, and heads of sub-villages and the criteria of research sample worked for at least 1 year with a minimum education of high school or equivalent. There was 83 respondents from 5 villages. The results of this study show that the competence of human resources had a positive but not significant effect on village fund accountability, there was a negative but not significant internal control effect on village fund accountability, there was a positive and significant influence on the use of technology on village fund accountability, and there was a positive but not significant effect community participation variable on accountability of village funds. The result of this study are expected to contribute to development of village fund accountability. While the urgency of this study relate information for the district government and the community so they know the principles of village fund accountability. Keywords: Village Fund, human resource competency, internal control, community participation, accountability.